Assignment of heme redox potentials of cytochrome CO3 from Desulfovibrio gigas by 2D NMR - Pereira, M. Antonieta Piçarra (1993)
Assignment of heme redox potentials of cytochrome CO3 from Desulfovibrio gigas by 2D NMR.